Design, construction and experimental work of a mini dissolved fuel alkaline fuel cell for micro-eletronic & mechanical signal application - Gan, Yong Kiong (University Malaysia Sarawak, (UNIMAS), 2004)
In the current project, a mini dissolved fuel alkaline fuel cell has been designed, constructed and laboratory tested. The purpose of the exercise is to design and construct a mini fuel cell for generating small amount of electricity. The voltage generated had been proven to be useful for micro-electronic and mechanical signal application i.e. the Pico Oscilloscope.